2018
DOI: 10.3390/educsci8020054
|View full text |Cite
|
Sign up to set email alerts
|

Looking Good and Being Good: Women Leaders in Australian Universities

Abstract: Abstract:In this article, I argue that women in senior leadership positions in universities continue to face a number of tensions and ambiguities in their everyday working lives. Drawing on the metaphors of 'looking good' and 'being good', I highlight the gendered assumptions that senior women encounter. As senior leaders, women are simultaneously required to negotiate an inherently masculine culture yet at the same time are expected to exercise a level of femininity. Their physical presence, appearance, cloth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…The grounds for selecting this track are “outstanding leadership” as evidenced by “projects, including strategic initiatives, which he/she has initiated and successfully implemented, the outcomes of those projects, and how those outcomes have impacted on the University’s performance” (Internal Promotional Documents, 2019). Given the under-representation of women in leadership positions in the Case Study University and the tendency for constructions of leadership to be gendered ( Schein, 1998 ; Fitzgerald, 2018 ; Gandi and Sen, 2021 ), this also seems unlikely to be helpful to women (it is little used by either: Athena SWAN application, 2017: 44).…”
Section: Resultsmentioning
confidence: 99%
“…The grounds for selecting this track are “outstanding leadership” as evidenced by “projects, including strategic initiatives, which he/she has initiated and successfully implemented, the outcomes of those projects, and how those outcomes have impacted on the University’s performance” (Internal Promotional Documents, 2019). Given the under-representation of women in leadership positions in the Case Study University and the tendency for constructions of leadership to be gendered ( Schein, 1998 ; Fitzgerald, 2018 ; Gandi and Sen, 2021 ), this also seems unlikely to be helpful to women (it is little used by either: Athena SWAN application, 2017: 44).…”
Section: Resultsmentioning
confidence: 99%
“…The methodology in these studies is broadly qualitative. Thus, for example, both Fitzgerald [9] and Carvalho and Diogo [10] use a narrative methodology; Harford [11] uses edited life stories within the life history research tradition; while Burkinshaw et al [12] use in-depth interviews and seminars. Acker and Millerson [7] use a highly innovative approach involving a collaborative autoethnography by a mother and daughter; while Peterson [13] uses a content and contextual analysis of job advertisements for Vice Chancellors.…”
Section: Current Volumementioning
confidence: 99%
“…Fitzgerald [9] focuses on the experiences of 30 senior leaders i.e., women in senior management positions including Deputy Vice Chancellors, Pro Vice Chancellors and Deans in Australia and New Zealand. She found that these women face a number of tensions and ambiguities in their everyday working lives revolving around 'looking good' and 'being good'.…”
Section: Current Volumementioning
confidence: 99%
“…The situation is similar also in the academic research sector. Researchers (Savigny, 2014;Fitzgerald, 2018;O'Connor, 2015;Burkinshaw and White, 2017), dealing with gender inequalities across countries, draw attention to significant differences in the proportion of women and men employed in research institutes, the disproportions among those achieving the highest academic degrees and their remuneration levels. Additionally, they underline that, even if the have higher positions, it is in a way perceived as "unnatural" or threatening to the stable order in the hierarchy.…”
Section: Introductionmentioning
confidence: 99%